Chemical Constituents of Anaxagorea Javanica and Their Antioxidant and Anti-Inflammatory Activities - Husain, Khairana (2008)
Anaxagorea javanica Blume (synonym A. scortechinii King) or locally known as ‘bunga pompun’, ‘kekapur’, ‘larak lecek’, ‘akar angin’, ‘kinchong’ or ‘atis’ is an endermic plant in Malaysia. The plant belongs to Annonaceae family and is traditionally used for the treatment after childbirth. Phytochemical investigation on the bark and root of this plant yielded seventeen pure compounds, comprising steroids, fatty acids, simple phenolics, alkaloids, flavonoids and sesquiterpenes. In total, seven alkaloids were isolated, out of which two new derivatives of copyrine alkaloid were 4,11-dimethoxyeupolauridine (87) and 2-methoxy-3-hydroxyeupolauridine (88) in addition to four known compounds, eupolauridine (22), 11- methoxyeupolauridine (86), sampangine (95) and 3-methoxysampangine (96). Another known alkaloid came from oxoaporphine was lysicamine (91). The isolation of copyrine and oxoaporphine alkaloids was a first time from the genus. Other known compounds isolated, included a mixture of β-sitosterol (49) and stigmasterol (94), quercetin (46), 7α-hydroxystigmasterol (92), 7-oxostigmasterol (93), 4-hydroxybutanamide (95), tetradecanoic acid (96), syringic aldehyde (97) and 2,3-dihydroxy-1-(4’-hydroxy-3’,5’-dimethoxyphenyl)-1-propanone (98). A novel sesquiterpene identified as 2,2,9-trimethyl-5-methylene-12-oxa-bicyclo[6.3.1]dodecane-4,9-diol (85) (nordine) was also isolated. All structures were elucidated by spectroscopic techniques and by comparison with data available from literature. Studies on the biological activities related to inflammation were conducted using nitric oxide (NO) and 5-lipoxygenase (5-LOX) inhibitory assay as a priminary screening as well as antioxidant assay. The results showed that both hexane and dichloromethane extracts from the barks possessed weak inhibition on NO production at the highest concentration of 200 μg/ml without cytotoxic effect. Meanwhile, inhibition of lipoxygenase activity was shown only by methanolic and acetone extracts from roots at 100 μg/ml with an IC50 of 48.21 and 63.87 μg/ml, respectively. However, all the crude extracts from barks and roots are poor radical scavenger inhibitors. Further in vitro investigation on the selected pure compounds showed that only sampangine (89) and 3- methoxysampangine (90) significantly inhibited NO production with IC50 values of 18.17 and 32.25 μg/ml, respectively, at the highest concentration of 25 μg/ml tested.